PENGARUH INTELLECTUAL CAPITAL DAN MARKETING CAPABILITY TERHADAP PROFITABILITAS DAN NILAI PERUSAHAAN DI SEKTOR PERBANKAN DAN KEUANGAN (KAPITALISASI BESAR) - Ammes Abel Widjanarko; Sarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to find out whether there was influence in the relationship between intellectual capital and marketing capability and used the company size and company age as control variables to test the affect of the variables on the profitability and the company's value. The variable intellectual capital measured by using the variables of its components, namely, human capital efficiency (HCE), structural capital efficiency (SCE), and the capital employed efficiency (CEE). Marketing capability (MC) measured by using the cost of marketing expenses and R & D expenses. The company's profitability measured by using the Return on Assets (ROA) ratio and the company's value measured by using Tobin's q (TQ) ratio. The sample used in the study was the companies registered in the banking sector and included into the category of large capitalization with the period of the study in 2009-2014 . The number of companies observed amounted to 37 companies with 185 firm years of observations. The hypothesis testing will be conducted using multiple linear regression analysis